Pengaruh Lingkungan Kerja dan Disiplin Kerja serta Motivasi Kerja Terhadap Kinerja Karyawan Perusahaan Daerah Air Minum (PDAM) Kabupaten Lumajang - Zainul Hidayat; Muchamad Taufiq (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2012)
The objectives of this research are : 1 ) to learn about the effect of Environment and Diciplin and Motivation to Performance at Perusahaan Daerah Air Minum Kabupaten Lumajang ; 2 ) to learn about the effect of Environment and Diciplin and Motivation partially to Performance at Perusahaan Daerah Air Minum Kabupaten Lumajang ; 3 ) to learn about the effect of Environment and Diciplin and Motivation that has dominant effect to Performance at Perusahaan Daerah Air Minum Kabupaten Lumajang. Where numbers of employee wich become the population are 60 persons respondent by spesialis. Data collection is by giving questionnaire toward respondents, interview upon organization member, and also viewing the document needed. The data collected is supported by assumption and reliability testing. The analysis model is supported by classic assumption testing ; multicolobierity test auto correlation test. To find out the accuracy of the model is by viewing determination coefficient, simultaneous hypothesis testing is taken by F test and partial hypothesis is taken by t test. From the double regression data analysis gained similarity regression line : Y = -1.435 + 0.330 X1 + 0.609 X2 + 0.156 X3 + e and founded that Hypothesis test result 1 : Fcount is 143.958 with probability 0,000 and Ftabel ( = 0,05; df 1=3; df2 = 60) is 2.769, it mean that Environment (X1) and Diciplin (X2) and Motivation ( X3) variables is simultan having effect to performance (Y), then the first hypothesis is accepted. Hypothesis 2 : Found that the value of tcount X1 is 3.059 and the value of ttabel is 2.003 and than tcount bigger the value ttabel 2.003, the second hypothesis is which stated about Environment (X1) and Diciplin (X2) and Motivation ( X3) variable is partially effect the performance (Y) is accepted. Diciplin (X2) is the dominantly variable wich giving effect toword performance with Standardized Coefficien Beta for variabel X2 is 0.425, it mean that performance (Y) can be exlaned by the variable of Diciplin (X2) there’s 42,5 percent. By that, the third hypothesis is accepted.